zeta(x,s)的一个恒等式

陈洪葛 posted @ Mar 13, 2014 05:42:15 PM in 数学分析 , 929 阅读

证明
\[ \sum_{n=1}^{\infty}\frac{(n-1)!}{n(x+1)(x+2)\cdots(x+n)}=\sum_{k=1}^{\infty}\frac{1}{(x+k)^2} \]
证明:
我们知道Gamma函数有
\[ \Gamma(x+1)=x\Gamma(x) \]
\[ \Gamma(x+n+1)=(x+n)(x+n-1)\cdots(x+1)\Gamma(x+1) \]
这样
\[ \frac{(n-1)!}{n(x+1)(x+2)\cdots(x+n)}=\frac{\Gamma(x+1)\Gamma(n)}{n\Gamma(x+n+1)}=\frac{B(x+1,n)}{n}\]
于是
\begin{align*}
\sum_{n=1}^{\infty}\frac{B(x+1,n)}{n}&=\sum_{k=1}^{\infty}\frac{1}{n}\int_{0}^{1}t^{n-1}(1-t)^{x}dt\\
&=\int_{0}^{1}\left(\sum_{n=1}^{\infty}\frac{t^{n-1}}{n}\right)(1-t)^{x}dt\\
&=\int_{0}^{1}\left[-\frac{\ln(1-t)}{t}\right](1-t)^{x}dt\\
&=\int_{0}^{1}\left[-\frac{\ln{z}}{1-z}\right]z^{x}dz \qquad (z=1-t)\\
&=\int_{0}^{1}(-1)\sum_{k=1}^{\infty}z^{x+k-1}\ln{z}dz\\
&=\sum_{k=1}^{\infty}(-1)\int_{0}^{1}z^{x+k-1}\ln{z}dz\\
&=\sum_{k=1}^{\infty}\int_{0}^{\infty}ue^{-u(x+k)}du\qquad (z=e^{-u})\\
&=\sum_{k=1}^{\infty}\int_{0}^{\infty}\frac{1}{(x+k)^2}ye^{-y}dy\qquad (y=u(x+k))\\
&=\sum_{k=1}^{\infty}\frac{1}{(x+k)^2}
\end{align*}


登录 *


loading captcha image...
(输入验证码)
or Ctrl+Enter